India through ages - Sareen, Tilak Raj, 1935-; Bakshi, S. R. (Shiri Ram), 1935- (New Delhi : Anmol Publications, 1992)
Contributed articles.
v. 1. Ancient culture and civilisation -- v. 2. Temples of India -- v. 3. Cities of India -- v. 4. Castes and tribes of India -- v. 5. Folklore of India.
Includes indexes.
Includes bibliographical references.
Keywords: India -- Civilization